Cubane-like tetranuclear Cu(ii) complexes bearing a Cu4O4 core: crystal structure, magnetic properties, DFT calculations and phenoxazinone synthase like activity. Issue 4 (6th January 2017) - Sagar, Shipra; Sengupta, Swaraj; Mota, Antonio J.; Chattopadhyay, Shyamal K.; Espinosa Ferao, Arturo; Riviere, Eric; Lewis, William; Naskar, Subhendu
Abstract : Two tetranuclear copper complexes with a Cu4 O4 cubane core exhibiting phenoxazinone synthase like activity are reported. Abstract : In the present work, two new copper complexes3a and3b with a Cu4 O4 cubane core are reported. Both complexes are obtained by means of the in situ conversion of the imine functionality of Schiff's base ligands1a [( E )-4-chloro-2-((thiazol-2-ylimino)methyl)phenol] and1b [( E )-4-bromo-2-((thiazol-2-ylimino)methyl)phenol] into amino alcohols2a (4-chloro-2-(hydroxy(thiazol-2-ylamino)methyl)phenol) and2b (4-bromo-2-(hydroxy(thiazol-2-ylamino)methyl)phenol), respectively. The ligand transformation may be metal assisted and the generated ligands show an interesting mode of coordination in which the alkoxo-O atom binds in a μ 3 -manner connecting simultaneously three copper centers and forming a Cu4 O4 cubane core. The first analysis of single crystal X-ray diffraction studies reveals that both molecules possess a [4 + 2] cubane-type core, and low temperature magnetic measurements show antiferromagnetic behaviour, in agreement with DFT calculations. However, the best fit and DFT calculations point out three pairs of coupling constants, more coherent with a [2 + 2 + 2] situation, in accordance with the fine analysis of structural data. Finally, phenoxazinone synthase activity has been measured for both molecules, finding k cat = 86.3 h −1 for the chloride derivative copper(ii ) complex in methanol, whereas the bromide derivative copper(ii ) complex displays k cat = 3.4026 × 10 2 h −1 and 10.289 × 10 2 h −1 in methanol and DMSO, respectively.